The Effectiveness of Ameliorant to Increase Carbon Stock of Oilpalm and Rubber Plantation on Peatland - Ai Dariah (UNIVERSITY OF LAMPUNG, 2015)
Application of peatland amelioration can improve soil quality, reduce GHG emissions, and increase carbon sequestration. The research aimed to study the effect of peatland amelioration on oil palm and rubber carbon stock improvement. Research was conducted from August 2013 until June 2014. The researches on oil palm were done in Arang-arang Village, Kumpeh Subdistrict, Muaro Jambi District, and in Lubuk Ogong Village, Bandar Seikijang Sub-district, Pelalawan District. Both sites are in Jambi and Riau Province. The research on rubber was done in Jabiren Village, Jabiren Raya Subdistrict, Pulang Pisau District, Central Kalimantan Province. The study used a Randomized Completely Block Design (RCBD), in four treatments and four replications. The treatments were pugam (peat fertilizer enriched by polyvalent cation), manure; empty fruit bunch compost, and control (no application). The measurement of C stock was performed 10 months after application using nondestructive methods. The results showed that peatland amelioration treatments had no significant effect to improve C stock on oil palm in 6 years old and 7 years old of rubber. After 10 months of amelioration application, the treatments increased C - stock of oil palm and rubber were 2.1-2.4 Mg ha-1 and 5-11 Mg ha-1, respectively. Longer time observation may be needed to study the effect of ameliorant on C-stock of annual crops.